Analysis of end use electrotechnology in mining and minerals processing as a determinant for electricity growth with special reference to the RSA - Davison, Marie Talitha (My University, 2017)
. The history of electricity growth in South Africa. has been one of rapid growth.' This reached as high as 13%in one year with the increase in electrification of mining and lndustry from the -1960's to 1980ts. In addition the development of new mines and new minerals beneficiation plants, especially metals beneficiation, accelerated electricity growth due to the electricity intensive end use technologies implemented that were specific to those industries
A project report submitted to the Faculty of Engineering, University of Witwatersrand, Johannesburg, In partial fulfilment of the requirements for the degree of Master of Science in Engineering George, 1996